Use of mineral particle film to protect ‘Okitsu’ tangerine and ‘Valencia’ orange against Anastrepha fraterculus and the effect on fruit quality - Cláudia Bernardes Ourique; Luiza Rodrigues Redaelli; Caio Fábio Stoffel Efrom; Mateus Pereira Gonzatto; Sergio Francisco Schwarz (Revista Ceres, 2022)
ABSTRACT The particle film technology has been reported as a promising tool in pest control. The objective of this work was to evaluate the efficiency of kaolin-based products against the oviposition of South American fruit fly, Anastrepha fraterculus (Dip.:Tephritidae), and its effect on the quality of citrus fruits. The experiment was conducted in orchards of ‘Okitsu’ tangerine and ‘Valencia’ orange trees in the 2017, 2018 and 2019 harvests. The treatments were as follows: 1) kaolin 10% + 0.1% Break-Thru® adjuvant; 2) Surround® 5% WP; 3) 0.15% phosmet (Imidan® 500 WP), 75 g. a.i.; 4) without application (control). The sprays were performed every 21 days. At harvest, fruits were individually packed in a greenhouse for inspection after 25 days and infestation was recorded. Fruit samples were evaluated for average diameter, average mass, soluble solids, titratable acidity and peel colorimetry. Infestation of A. fraterculus in tangerines was reduced in plants treated with the two kaolin-based products in the 2017 harvest. In the 2017 and 2019 crops, Surround® WP reduced the infestation and the number of puparium/fruits in oranges. The mineral films did not alter the physicochemical characteristics of the fruits, representing a promising alternative for the management of A. fraterculus.